IMPROVING DATA MANAGEMENT FOR ENVIRONMENTAL REPORTING IN THE GOLD MINING INDUSTRY - Janse van Rensburg, Hendrika Magdalena Maryke; Gous, Andries Gustav Stephanus; Vosloo, Jan C; van Heerden, Mariska (The South African Journal of Industrial Engineering, 2019)
Environmental reporting is a realistic alternative for mines to prioritise operational changes in crucial environmental areas. Gold mines report to multiple platforms – i.e., integrated reporting. All these platforms have created the need for effective environmental data management. A methodology was developed in which the environmental performance data for numerous operations is centralised. A standardised reporting procedure was developed for each environmental data category that includes the different stakeholders’ needs. Focus was also placed on reducing the data transfer errors due to the importance of data accuracy. The methodology is based on the plan-do-check-act (PDCA) cycle and was implemented at a gold mining company. After implementation, the rate of transfer error that would have been recorded in the data was reduced from 20 percent to four percent. This error rate was recorded before an external audit took place.